2019
DOI: 10.1115/1.4045600
|View full text |Cite
|
Sign up to set email alerts
|

Does Visual Fixation Affect Idea Fixation?

Abstract: Divergent thinking, an aspect of creativity, is often studied by measuring performance on the Alternative Uses Test (AUT). There is, however, a gap in creativity research concerning how visual stimuli on the AUT are perceived. Memory and attention researchers have used eye-tracking studies to reveal insights into how people think and how they perceive visual stimuli. Thus, the current work uses eye tracking to study how eye movements are related to creativity. Participants orally listed alternative uses for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Creative processes and results are influenced by creativity components (creative motivation, creative thinking, and professional conition) (Amabile, 1997;Ramos et al, 2018;Sternberg, 1999). VR technology can be used for dynamic demonstrations and interactions in the form of three-dimensional display tools (Kwon et al, 2020;, thereby guaranteeing greater creative freedom (Fleury et al, 2020;Fröhlich et al, 2018). Students can develop their creativity by using entertaining and stimulating design-assisting tools.…”
Section: Creative Performancementioning
confidence: 99%
“…Creative processes and results are influenced by creativity components (creative motivation, creative thinking, and professional conition) (Amabile, 1997;Ramos et al, 2018;Sternberg, 1999). VR technology can be used for dynamic demonstrations and interactions in the form of three-dimensional display tools (Kwon et al, 2020;, thereby guaranteeing greater creative freedom (Fleury et al, 2020;Fröhlich et al, 2018). Students can develop their creativity by using entertaining and stimulating design-assisting tools.…”
Section: Creative Performancementioning
confidence: 99%
“…A recent study has shown links between visual behaviour and divergent creativity (Kwon, Ryan, Bazylak & Shu, 2020). However, these were based on different views of the images related to the GAU test.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (2018) also uses stimuli of varying distance from the problem space to explore difference between beginning and advanced design students during idea generation, but uses images as stimuli. Kwon et al (2019) looked into the relation of eye movements and idea output (creativity) to an "alternative uses test (AUT)", where participants are presented with 12 object images and get 2 minutes per object to name alternative uses of the object.…”
Section: Similar Researchmentioning
confidence: 99%